2021
DOI: 10.1002/em.22428
|View full text |Cite
|
Sign up to set email alerts
|

Differences in cell death in methionine versus cysteine depletion

Abstract: Restriction of the sulfur amino acids methionine and cysteine has recently been proposed as potential adjuvant therapy in cancer. While cysteine depletion has been associated with ferroptotic cell death, methionine depletion has not. We hypothesized that comparing the response of melanoma cell lines to depletion of the amino acids methionine and cysteine would give us insight into the critical role in cancer of these two closely related amino acids. We analyzed the response to three conditions: methionine depl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 23 publications
5
18
0
Order By: Relevance
“…An siRNA screen for suppressors of ferroptosis in 2016 revealed that the top hit was the knockdown of CARS, the cysteinyl-tRNA synthetase, which suppressed erastin-induced ferroptosis through activating the transsulfuration pathway (Hayano et al, 2016). The transsulfuration pathway metabolite homocysteine was reported to enhance ferroptosis rather than drive resistance to ferroptosis when supplemented in the culture medium (Wallis et al, 2021).…”
Section: Ll Open Accessmentioning
confidence: 99%
“…An siRNA screen for suppressors of ferroptosis in 2016 revealed that the top hit was the knockdown of CARS, the cysteinyl-tRNA synthetase, which suppressed erastin-induced ferroptosis through activating the transsulfuration pathway (Hayano et al, 2016). The transsulfuration pathway metabolite homocysteine was reported to enhance ferroptosis rather than drive resistance to ferroptosis when supplemented in the culture medium (Wallis et al, 2021).…”
Section: Ll Open Accessmentioning
confidence: 99%
“…Cysteine is one of the most important amino acids involved in the maintenance of the redox balance, since it takes part in the synthesis of glutathione (GSH) [ 27 ]. After AgNPs exposure, cysteine levels were found depleted (RM = 0.33); this has been linked to impaired cellular growth and cellular death due to the proliferation of oxidative stress and the limitation of iron-sulfur clusters, which are necessary for the electron transport chain (ETC) operation [ 28 , 29 ]. The low levels of cysteine might be explained by the downregulation of the CBS transcript (FC = 0.37) which is a key enzyme involved in the transsufuration pathway that, alongside CTH (FC = 0.70), also found to be downregulated, leads to the formation of cysteine.…”
Section: Discussionmentioning
confidence: 99%
“…The biosynthesis of amino acids pathway is crucial in the ferroptosis mechanism [21][22][23][24][25].GSH is synthesized from three key amino acids, cysteine, glutamate, and glycine [26,27]. Both glycine and cysteine can be produced through the metabolic axis from glucose to serine.…”
Section: Discussionmentioning
confidence: 99%